Experimental research on enhancing effectiveness in teaching the nature of seasons - Melike Güzin Semercioğlu; Hüseyin Kalkan (Discover Education)
Abstract In recent years, studies by education researchers indicate that, despite various instructional methods to enhance the conceptual understanding of seasons, the reasons for the formation of seasons and the processes involved are still not fully grasped. This research aims to investigate the fundamental reasons for the difficulties in comprehending the formation of seasons and to develop possible solutions. To achieve this goal, a physical model based on the “Change in the Amount of Energy Falling onto a Unit Surface (CAEFUS)” of parallel beams of sunlight as Earth orbits around the Sun with a tilted axis of approximately 23.5 degrees was developed and applied to participants, and data were collected. These instructional processes were applied to experimental and control groups. The research was conducted on 148 eighth-grade students in a state school in Samsun (the city in Turkey) province. Exploratory factor analysis was used to analyze students' drawings and separate them into their most prominent elements. The quantitative data analysis, consisting of multiple-choice questions, utilized the SPSS 22.0 statistical program. According to ANOVA Results for SEMAT Achievement Scores, a significant difference was determined between the experimental and control groups (F = 7.625, p < 0.05). In addition, the control group mean in the pre-test fell below the experimental group mean in the pre-test. However, the mean of the experimental group in the post-test exceeded that of the control group (Pre-test‘e’ = 1.54, Pre-test‘c’ = 1.82; Post-test‘e’ = 3.21, Post-test‘c’ = 2.86). The data analysis revealed that the CAEFUS-based model significantly impacted the meaningful teaching of the nature of seasons. These results were thoroughly evaluated through a detailed comparison with the literature.